SOSIALISASI PENGGUNAAN ALAT BRT DR SEBAGAI BAHAN BAKAR TERBARUKAN UNTUK RUMAH TANGGA - Ilmardani Rince Ramli (Jurnal Ilmiah Padma Sri Kreshna, 2019)
With human development and developing era with the passing of time and the development of Â science human life and energy needs of developing any rise in world oil prices is very influential on the lives of the people of indonesia.The government immediately took steps to take fuel subsidies with the direct impact on the people of the village every day in need of energy for household needs. With this, there must be (renewable) alternative fuels for the solution with appropriate technology that is effective, efficient and environmentally friendly, namely by making a DR BRT tool to process cow manure into gas for daily needs for the community to cook, electricity in accordance with the situation and condition of the community that has the basic ingredients of cow dung waste, with community service using the DR BRT tool around the abang temple, sentonorejo jogotirto berbeman Yogyakarta can utilize cow manure to be processed into gas with appropriate tools. (keywords: appropriate technology, BRT DR, cow manure, environmentally friendly).